Comparative transcriptomic profiling in the pulp and peel of pitaya fruit uncovers the gene networks regulating pulp color formation - Li, Xiaomei; Tang, Yayuan; Li, Li; Liang, Guidong; Li, Jing; Liu, Chaoan; He, Xuemei; Sun, Jian (Frontiers in Plant Science, 2022)
Pitaya (genus Hylocereus) is a popular fruit. To develop pitaya fruit with greater marketability and high nutritional value, it is important to elucidate the roles of candidate genes and key metabolites that contribute to the coloration of the pitaya pulp and peel. By combining transcriptome and biochemical analyses, we compared and analyzed the dynamic changes in the peel and pulp of H. undatus (white pulp) and H. polyrhizus (red pulp) fruits at four key time points during ripening. Differential expression analysis and temporal analysis revealed the difference regulation in pathways of plant hormone signal transduction, phenylpropanoid biosynthesis, and betalain biosynthesis. Our results suggest that color formation of purple-red peel and pulp of pitaya is influenced by betalains. Increased tyrosine content and fluctuation in acylated betalain content may be responsible for pulp color formation, while some of the key genes in this network showed differential expression patterns during ripening between white pulp and red pulp fruits. The data and analysis results of this study provide theoretical basis for the red color formation mechanism of pitaya, which will facilitate future work to improve pitaya fruit physical appearance and marketability.